Gender equality in Latin America - S. M. Rebrey (Ибероамериканские тетради)
The article concerns measuring gender equality in Latin American countries based on statistics from international (WEF, OECD, ILO, UNESCO) and regional (UNECLAC) organizations and national statistical services, as well as various gender inequality indices (GGI, SIGI). Gender equality is seen as one of the goals of sustainable development, and gender inequality – as a brake on its path. The study is conducted within institutional approach, since institutions are formal and informal restrictions accepted in society and determine the scale and factors of gender inequality. Particular attention is paid to axial institutions that play a primary role in creation, formation and implementation of human capital, namely the institutions of the family and the labor market, education and science, state and corporate governance. The study shows that, among emerging economies, Latin America has very high levels of gender equality as a result of a high degree of feminization of labor markets among other factors. However, the predominance of traditional division of labor in institution of the family levels out the bonuses from participation of women in paid work and exacerbates the problem of a double burden: women are caught in a vise, where, on the one hand, there is a paid work, and, on the other, an unpaid domestic work, which falls mainly on women. The most significant factor that positively affects the increase in gender equality is the share of women in government, while the level of socio-economic development of the country without a specialized policy aimed at stimulating gender equality does not lead to an increase in the latter.